TINJAUAN SAKRALITAS KEPEMIMPINAN PENDIDIKAN DALAM PERSPEKTIF AL-QUR’AN - Yeni Tri Nur Rahmawati (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2017)
The problem dealt with in this research is quranic educational leadership related with educational leadership principles; sacred, profane and combined one. This research uses quranic verses concerning educational leadership. The method used in collecting data is recollecting, arranging, describing, and mentioning leadership concept. Techniques used to verify data are observation, triangulation technique, colleague verifying technique, and content analysis. Steps for this research are done by collecting, investigating, deciding, and amalgamating Quranic verses to search leadership concept within it. This research is bibliographical research with mawdu’iy method and explorative qualitative approach to reconstruct. This research results in several following conclusions: first, sacred leadership has six terms, that is, Al-Malik, Al-Hada, Al-Wala, Al-Rabb, Al-Qahhar and Al-Kabar. These terms have six advantages –responsibility and mercy in the hereafter and this world and flipsides – in human kind point of view there is less democracy (syura), justice (‘adalah), freedom (hurriyah), equality (musawa), and guaranted availability of absolute perfectness. Secondly, profane leadership has eight terms; Khalifah, Ulil Amri, Mala’, Im_mah, Sultan, Naqab, Sadah, and Qawwaman. These terms have disanvantages–responsibility and mercy only in this world and plus point –there is more democracy (syura), justice (‘adalah), freedom (hurriyah), equality (musawa), and there is no guaranted availability of absolute perfectness. Thirdly, educational leadership, which combines sacred and profanity, creates realistic educational leadership. Integration between human’s submission to God and his rationality brings him to happiness in this world and the hereafter. Hence, combination of sacred and profane educational leadership produce the leadership of “Khalifah Rububiyah” which is equilibrium between sacred teachings and reality in this world. Thus, the principles; democracy, (syura) justice, (‘adalah) freedom (hurriyah) and equality (musawa) in educational leadership can be achieved optimally based on responsibility and mercy in this world and hereafter and guarantee of this world perfectness.